Contraction of global carbon emissions: how acceptable are alternative emission entitlement schemes - Christoph Böhringer; Heinz Welsch (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
The allocation of emissions entitlements across countries is the single most controversial issue in international climate policy. Extreme positions within the policy debate range from entitlement based on current emission patterns (CEP) to equal-per-capita (EPC) allocations.Convergence (COV) from an initial CEP allocation towards EPC emission rights represents a reconciliation of the two. This paper maintains that the acceptability of alternative entitlement schemes depends on their implications for economic welfare and uses a dynamic multi-region general equilibrium model for a comparative economic assessment of the above allocation rules. We find welfare implications for the varius regions to be strongly influenced by changes in the terms of trade. Especially, regions may experience considerable welfare losses even under entitlement schemes which impose no binding emission constraint on them. Among the arrangements examined, COV cum emissions trading stands out for offering the developing countries substantial incentives for paticipation in the international greenhouse gas abatement effort without imposing excessive burdens on the industrialized countries.
Keywords: D58; Q4; Q2; 330; climate policy; economic welfare; international equity; emissions trading; computable general equilibrium modeling; Klimaschutz; Luftreinhaltung; Emissionsrechte; Wirtschaftspolitische Wirkungsanalyse; Wohlfahrtseffekt; Allgemeines Gleichgewicht; Welt